Sustainable Pest Management Through Preventive Conservation: Case Studies in the Natural History Museum o - Chiwara, Davison (Taylor and Francis Ltd., 2021)
Sustainable Pest Management Through Preventive Conservation: Case Studies in the Natural History Museum of Zimbabwe and the Zimbabwe Military Museum